EXPORT COMPETITIVENESS OF INDIAN SPIRITS: THE METHOD OF REVEALED COMPARATIVE ADVANTAGE (RCA) WITH SPECIAL REFERENCE TO WINE - Arora, Dr. Anudeep; Batra, Prof. (Dr.) Durgesh; Khanna, Ms. Trishali; Tandon, Dr. Vandana (The journal of contemporary issues in business and government, 2022)
In this research paper, wine's export competitiveness is analyzed. Indian vineyards are the fastest-growing agricultural sector in the country, with the seventh-highest productivity. India has a comparative advantage in agriculture and expanding agro-based exports can significantly increase agricultural returns and employment. A REVEALED COMPARATIVE ADVANTAGE study framework is used in order to assess the structural transformation in India's share of the global export market in terms of competitiveness and structural repercussions during 2001-to 2021. The REVEALED COMPARATIVE ADVANTAGE Approach is extensively used to empirically evaluate a country's export performance. With the technique used, the process of benchmarking International and Intra-national exports is made much easier. In a multitude of contexts, the key competencies can be used to model industrial export competitiveness. Using the REVEALED COMPARATIVE ADVANTAGE METHOD, this paper attempts to determine a region's export potential.